Le privé est politique… et économique ! Pour une économie politique du travail de gestation pour autrui: - Jouan, Marlène; Clos, Clémence (Nouvelles Questions Féministes, 2021)
Dans le débat public sur la gestation pour autrui (GPA), parler de « travail » pour qualifier ce que font les femmes porteuses est largement perçu comme une façon de cautionner les formes de marchandisation et d’exploitation du corps des femmes à l’œuvre dans les circuits mondialisés de la bioéconomie. Contre cette interprétation qui accompagne la condamnation morale de cette pratique reproductive, en particulier dans sa version « commerciale », l’article développe une défense féministe de la conceptualisation de la GPA comme travail, appuyée sur les études ethnographiques menées auprès des femmes porteuses indiennes et nourrie théoriquement à la fois par le marxisme, par l’éthique du care et par la notion d’intersectionnalité. In fine, l’objectif est de mettre en lumière la fécondité de cette conceptualisation non seulement pour la pleine reconnaissance des femmes porteuses, mais aussi pour le diagnostic critique des divisions du travail qui structurent la société capitaliste.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; asie; care; corps; cours; discipline; europe; france; inde; inégalités; maternité; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social